Analysis of the Effect of Sustainable Agricultural Investment Planning Model on Agricultural Development in Indonesia - Puspita, Nurul; Maulana, Muhammad Akbar; Widyatama, Hedy Ilham (Economics and Business International Conference Proceeding, 2024)
Planning a sustainable agriculture investment model is essential to address global challenges such as climate change, land degradation, and increasing food demand. The purpose of this research is to design a sustainable agricultural investment model using bibliographic analysis method. Bibliographic analysis was used to identify research trends, collaboration networks, and key themes related to sustainable agricultural investment from various scientific publications published between 2015 and 2024. Data were collected from major scientific databases and analyzed using bibliometric software. The results show that the number of publications on this topic has increased significantly over the past decade, with increasing emphasis on the integration of advanced technologies, government policies and environmentally friendly agricultural practices. These findings provide a basis for designing an investment model that not only optimizes crop yields but also considers social and ecological aspects. This proposed model will help policy makers, investors, and farmers make better decisions towards sustainable and competitive agriculture. Investment models that potentially provide opportunities for sustainable agriculture in Indonesia include food estate, agritourism, climate intelligence, organic, agroforestry, and agroecology. These investment models are expected to solve problems related to sustainable agriculture in Indonesia.